2012
DOI: 10.4236/fns.2012.38153
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Response of Type 2 Diabetics to Raisins

Abstract: Background: Raisins are a nutritious fruit snack containing fiber, antioxidants, and potassium. Diabetics tend to have low fruit intakes, possibly due to concerns about glycemic response. Aim: This study sought to characterize the utility of raisins as a way to improve fruit consumption by type 2 diabetics. Methods: Fasting type 2 diabetics randomly received 100 Calorie servings of bananas (BA; 103.1 g), white bread (WB; 40.2 g), raisins (RA; 30.3 g), or Thompson seedless grapes (TG; 112.4 g) on each of four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In particular, dried fruit products are essential sources of dietary fibre and potassium with low levels of fat (0.32–0.93 g per 100 g) [1]. They are rich in sugars such as fructose and glucose, and carbohydrates, with low (<55) or moderate (from 56 to 69) insulin and glycaemic indices, comparable to fresh fruit ones, as demonstrated by different studies [8,9]. Low levels of insulin/glycaemic index are due to the presence of several substances (e.g., phenolic acids, tannins, and fibre) which may moderate the glycaemic and insulin response [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, dried fruit products are essential sources of dietary fibre and potassium with low levels of fat (0.32–0.93 g per 100 g) [1]. They are rich in sugars such as fructose and glucose, and carbohydrates, with low (<55) or moderate (from 56 to 69) insulin and glycaemic indices, comparable to fresh fruit ones, as demonstrated by different studies [8,9]. Low levels of insulin/glycaemic index are due to the presence of several substances (e.g., phenolic acids, tannins, and fibre) which may moderate the glycaemic and insulin response [5].…”
Section: Introductionmentioning
confidence: 99%
“…The use of dried fruit – raisins especially – to control blood glucose and with reference to suitability as a snack for diabetics has been studied and reviewed by others. Anderson and coworkers 40 indicated that the healthy glycaemic and insulin response and ease of use of raisins makes them attractive for improving fruit consumption in type 2 diabetics. Anderson and Waters 41 also discussed the role of raisins in the diet in more detail in the context of blood pressure control, cardiovascular benefits and blood glucose control.…”
Section: Sugar As An Ingredient Versus In Dried Fruitmentioning
confidence: 99%
“…A single-crossover study found little difference between the glycemic responses to 100-cal servings of grapes or raisins among subjects with type 2 diabetes. Insulin AUC value for raisins was lower than that for grapes (2970 ± 849 and 3960 ± 1370), but the difference was not significant [ 39 ].
Fig.
…”
Section: Reviewmentioning
confidence: 99%